Electrical engineer's reference book. - Laughton, M. A. (Michael A); Say, M. G. (Maurice George), 1902-1992 (Butterworths, 1985)
Electrical Engineer's Reference Book, Fourteenth Edition focuses on electrical engineering. The book first discusses units, mathematics, and physical quantities, including the international unit system, physical properties, and electricity. The text also looks at network and control systems analysis. The book examines materials used in electrical engineering. Topics include conducting materials, superconductors, silicon, insulating materials, electrical steels, and soft irons and relay steels. The text underscores electrical metrology and instrumentation, steam-generating plants, turbines and.